PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN PENGUJIAN KENDARAAN BERMOTOR DI DINAS PERHUBUNGAN KAB. BLITAR (Manajemen & Bisnis Jurnal, 2023)
Abstract. Motor vehicle testing is an important thing to test the roadworthiness of a goods vehicle or person with certain provisions. This study discusses the quality of service and customer value on customer satisfaction by using motor vehicle testing services at the District Transportation Office. Blitar. The population of this study was taken from the test applicants and the samples used in this study were 73 respondents. The sampling technique used is probability sampling with the type of sampling that is Simple Random Sampling. The analytical method used in this study is using multiple linear regression with the help of the Statistical Package for Social Sciences (SPSS). The results of the Hypothesis Test indicate that service quality and customer value have a significant positive effect on customer satisfaction